Development of Multi-Waste Briquettes as an Emission Reduction Strategy in Citronella Oil Refinery at PT Arutmin Indonesia - Kurniawan Shidiq; Tsani Adiyanti; Kevin Tanjung; M. Indra Darmawan; Hamdan Auli; Qomarudin Sukri; Meldayanoor (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2025)
The demand for environmentally friendly alternative energy continues to increase in line with the depletion of fossil fuel availability and its environmental impacts. One potential solution is the utilization of biomass-based bio briquettes as a renewable energy source. This study aims to evaluate the quality of biobriquettes through seven key parameters, namely moisture content, ash content, density, volatile matter, burning rate, calorific value, and emission test, which were compared to the Indonesian National Standard (SNI) as well as firewood combustion results. A quantitative descriptive method was employed using three formulations with three replications. The results showed that the moisture content (10.00–13.33%) and ash content (10–15.67%) met the requirements of SNI 4931:2010. The density of the bio briquettes (0.42–0.552 g/cm³) indicated a reasonably good compactness although no SNI reference is available for density. However, the volatile matter content remained considerably high (65.33–76.33%), exceeding the SNI threshold of <22%. The burning rate ranged from 0.0058–0.0066 g/s with stable combustion characteristics. The calorific value of the bio briquettes was between 2760.21–3387.41 Cal/g, while emission tests showed the highest CO concentration at 0.86% in FP1, CO₂ at 3.37% in FP2, O₂ at 20.95% in FP2, and HC at 139.33 ppm in FP1.